The Control Of Gadget Use At Gagas Ceria Bandung Elementary School Indonesia As An Anticipation Toward Negative Impacts Of Social Media - Gustini, Leili Kurnia (2015)
The existence of gadget is like the two sides of a coin. On one side, it brings benefits to our life, but on the other side, it facilitates negative impacts to its users. The adults have at least been wise in their use of gadgets, children are on the contrary. Children are generally at their age of exploring the world beyond themselves, regardless their lack of knowledge and wisdom to sort the positive instead of the negative ones. In this research, the author presents an incident occured at one of the private schools in Bandung, Indonesia, that is Gagas Ceria Elementary School. Gagas Ceria Elementary School is a modern school supported by technology media in its daily learning process. An incident has made a rule to emerge at this school. The rule says “Gadget Use is Strictly Controlled.” As the trend of chatting-room goups and social media is growing children at elementary school age follows this trend as well. From 54 fourth-grader students, 34 of them joined ‘ Line’, a social media chatting-room. They intended to make social-media chatrooms as a medium to communicate with each other, but in fact, the chatrooms are contaminated by bullying content from some particular children to the others.